AVALIAÇÃO PÓS-COLHEITA EM CONSÓRCIO DE ALFACE X RÚCULA COM O USO DE ESTERCO BOVINO - De moraes, Reginald; Ribera, Laura; Ramires, Lucas Richard; Cardoso, Sanara; Sakissaka, Roberto Carlos; Da Silva, Maiele (ANAIS DO ENIC, 2018)
-